A kind of degradable plastic masterbatch and its preparation and application

Through the technical means of modifying the puerar fiber and polylactic acid composite, the existing degradable plastics have poor mechanical properties, high water absorption and poor UV resistance, and have achieved stronger mechanical properties, lower water absorption and better UV resistance, which are suitable for large-scale industrial applications.

CN118667314BActive Publication Date: 2025-04-25GUANGDONG MINGJU NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410802419.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-04-25
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

The existing biodegradable plastics have poor mechanical properties, high water absorption rate, and poor UV resistance, making it difficult to meet the needs of large-scale industrial applications.

Method used

By using modified Pueraria fiber and polylactic acid composite material silanized after alkali treatment, combined with KH-550 and NaOH treatment, the interface bonding strength and interface friction between the modified Pueraria fiber and the polylactic acid matrix are greatly improved, thereby improving the mechanical properties and ultraviolet resistance of the plastic.

Benefits of technology

It significantly improves the mechanical properties of the degradable plastic, reduces the water absorption rate, and significantly improves the UV resistance, making it more suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0004903747150000021
    Figure BDA0004903747150000021
Patent Text Reader

Abstract

The present invention relates to a degradable plastic masterbatch and its preparation and application. The degradable plastic masterbatch comprises the following components by weight: 0.1 to 15 parts of modified kudzu fiber, 80 to 95 parts of polylactic acid, 5 to 15 parts of starch, and 0.5 to 2 parts of coupling agent. Compared with the prior art, the present invention has the advantages of better mechanical properties, lower water absorption, better UV resistance, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of degradable plastics, and in particular to a degradable plastic masterbatch and the preparation and application thereof. Background Art

[0002] Plastics are widely used in agriculture, architecture, construction and consumer products, playing a vital role in various industries, such as packaging for food, medicine, detergents and cosmetics. However, excessive consumption of plastics has a great impact on the ecosystem on Earth, so a degradable plastic is urgently needed to solve the above problems.

[0003] For example, CN116144191A discloses a degradable plastic prepared from plant wood fiber and a preparation method thereof, which belongs to the field of degradable plastic preparation, including a degradable plastic prepared from plant wood fiber and a preparation method of a degradable plastic prepared from plant wood fiber. After dissolving plant wood fiber, high molecular weight polyethylene glycol and polyethyleneimine in a plant wood fiber solution, adding water precipitates a large amount of stable solid plastic particles containing cellulose lignin and high toughness.

[0004] CN111848998A discloses an environmentally friendly degradable cotton cellulose plastic film and a preparation method thereof, wherein the environmentally friendly degradable cotton cellulose plastic film is prepared by using nitrided wood cellulose, hydroxypropyl starch, hydroxyethyl cellulose, polyethylene and polylactic acid fiber.

[0005] For example, CN106118000A discloses a nano-carbon aerogel-modified cyanobacteria-based composite bioplastic and a preparation method thereof, comprising the following components in parts by weight: 130-135 cyanobacteria, 9-10 Lactobacillus casei, 7-8 spores of Pycnoporus sanguinosa, 10-11 shellac, 8-9 nano-carbon aerogel, 16-17 glucose, 56-58 salmon collagen, 36-38 nitrocellulose, 12-13 tourmaline powder, 28-30 polyaspartic acid, 9-10 alkyl ketene dimer, 8-9 stearic acid, and an appropriate amount of water.

[0006] However, the above-mentioned modified biodegradable plastics have poor mechanical properties, high water absorption, and poor UV resistance, which are far from being applicable to large-scale industrial applications. Summary of the invention

[0007] The purpose of the present invention is to provide a degradable plastic masterbatch and its preparation and application in order to overcome the poor mechanical properties, high water absorption and poor UV resistance of the above-mentioned prior art.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] The first aspect of the present invention provides a degradable plastic masterbatch, comprising the following components in parts by weight:

[0010]

[0011] Furthermore, the degradable plastic masterbatch comprises the following components in parts by weight:

[0012]

[0013] Furthermore, the particle size of the modified kudzu fiber is 500 μm to 2700 μm;

[0014] Wherein, the molecular weight of the polylactic acid is a weight average molecular weight of 5 to 19×10 5 g / mol;

[0015] Wherein, the coupling agent is one or more of KH550 silane coupling agent, KH560 silane coupling agent, KH570 silane coupling agent, titanate coupling agent TTS, titanate coupling agent 201, and aluminate coupling agent.

[0016] Furthermore, the modified kudzu fiber is specifically prepared by treating the kudzu fiber with an alkali solution, then silanizing the obtained solid phase, and washing and drying it.

[0017] Furthermore, the alkali solution treatment of the kudzu fiber specifically includes: mixing the kudzu fiber and a sodium hydroxide solution, ultrasonicating for 0.5 to 1.5 hours, washing, freeze-drying, and obtaining a solid phase; wherein the pH of the alkali solution is 9 to 11, preferably 10;

[0018] The silanization of the solid phase specifically includes: mixing the solid phase and silanol, stirring at 40-60° C. for 2-3 hours, washing, freeze-drying, and obtaining the modified kudzu fiber.

[0019] The second aspect of the present invention provides a method for preparing a degradable plastic masterbatch, comprising the following steps:

[0020] The coupling agent is stirred and mixed with starch, and then stirred and mixed with modified kudzu fiber and polylactic acid. The solid phase is then added into a twin-screw extruder unit for mixing and extrusion. The extruded long strip sample is pelletized, and the pelletization is repeated at least once.

[0021] Furthermore, the mass ratio of the modified kudzu fiber, polylactic acid, starch, and coupling agent is (0.1-15): (80-95): (5-15): (0.5-2);

[0022] Wherein, the molecular weight of the polylactic acid is a weight average molecular weight of 5 to 19×10 5 g / mol;

[0023] Wherein, the coupling agent is one or more of KH550 silane coupling agent, KH560 silane coupling agent, KH570 silane coupling agent, titanate coupling agent TTS, titanate coupling agent 201, and aluminate coupling agent;

[0024] The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 0.5 to 1.5 hours, washing and freeze-drying to obtain a solid phase, wherein the pH of the alkaline solution is 9 to 11, then mixing the solid phase and silanol, stirring at 40 to 60° C. for 2 to 3 hours, washing and freeze-drying to obtain the modified kudzu fiber.

[0025] Furthermore, the coupling agent and starch are mixed at a temperature of 80 to 120° C., a mixing time of 10 to 20 min, and a mixing container is a high-speed mixer;

[0026] The mixing temperature with the modified kudzu fiber and polylactic acid is room temperature, the mixing time is 5 to 10 minutes, and the mixing container is a high-speed mixer;

[0027] The twin-screw extruder has a screw length-to-diameter ratio of 40 to 60 and a screw speed of 20 to 40 rpm.

[0028] Among them, the temperatures of the eight heating zones and the die head of the twin-screw extruder unit are 130, 135, 140, 145, 150, 160, 165, 165, and 155° C. respectively.

[0029] The third aspect of the present invention provides a degradable plastic masterbatch obtained by the preparation method of the degradable plastic masterbatch as described above.

[0030] A fourth aspect of the present invention provides a use of the above-mentioned degradable plastic masterbatch in the preparation of plastic film.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The biodegradable plastic masterbatch provided by the present invention has good mechanical properties, the interface bonding strength between the modified kudzu fiber and the polylactic acid composite material is large, and the interface bonding strength is strong, so that the plastic has strong mechanical properties, and the friction force at the interface between the modified kudzu fiber and the polylactic acid composite material is greater, so that the plastic has better mechanical properties.

[0033] 2. The degradable plastic masterbatch provided by the present invention has a low water absorption rate. The number of hydroxyl groups on the surface of the modified kudzu fiber is reduced by treating with KH-550 and NaOH, so that the modified kudzu fiber is evenly dispersed in the polylactic acid matrix, making the formed plastic surface smoother and preventing water molecules from entering the plastic. On the other hand, the modification treatment makes the surface of the kudzu fiber rough, making the modified kudzu fiber and polylactic acid more tightly bonded, reducing the gap between the modified kudzu fiber and the polylactic acid matrix, thereby preventing water molecules from diffusing between the modified kudzu fiber and the polylactic acid.

[0034] 3. The biodegradable plastic masterbatch provided by the present invention has good ultraviolet shielding performance. Adding modified kudzu root fiber can effectively improve the ultraviolet shielding performance of plastic. This is because the fiber absorbs ultraviolet rays, and the modified kudzu root fibers agglomerate and entangle with each other and also effectively shield ultraviolet rays. DETAILED DESCRIPTION

[0035] For ease of understanding of the present application, the present application will be described more fully below by way of embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0036] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined as its own lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unclearly recorded range.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.

[0038] In the existing technology, biodegradable plastics have poor mechanical properties, high water absorption, and poor transparency, which are far from being suitable for large-scale industrial application.

[0039] It should be noted that the processing method of Pueraria fiber is as follows:

[0040] Soak the kudzu root residue for a short time. Specifically, place the kudzu root residue raw material in a beaker, add an appropriate amount of water, at least immerse the added kudzu root residue raw material, soak for 1 to 4 days, preferably 2 days, or observe that the kudzu root residue is dispersed, that is, soaking is complete. Then wash the soaked kudzu root residue and collect the solid phase by centrifugation, wherein the washing is rinsed with distilled water and anhydrous ethanol for multiple times, at least 3 times, and then filter and collect the solid phase after centrifugation, and then put it into a blast drying oven to dry at 80°C for 24 hours, and then use a pulverizer to crush the dried kudzu root residue, and sieve to obtain kudzu fiber with different particle sizes.

[0041] Based on this, the first aspect of the embodiment of the present application provides a degradable plastic masterbatch, comprising the following components in parts by weight:

[0042]

[0043] In some embodiments, the degradable plastic masterbatch comprises the following components in parts by weight:

[0044]

[0045] Preferably, the degradable plastic masterbatch comprises the following components in parts by weight:

[0046]

[0047] In some embodiments, the particle size of the modified kudzu fiber is 500 μm to 2700 μm, preferably 500 μm, and the molecular weight of the polylactic acid is a weight average molecular weight of 5 to 19×10 5 g / mol, the starch is corn starch or cassava starch, preferably corn starch, and the coupling agent is one or more of KH550 silane coupling agent, KH560 silane coupling agent, KH570 silane coupling agent, titanate coupling agent TTS, titanate coupling agent 201, and aluminate coupling agent, preferably KH550 silane coupling agent.

[0048] In some embodiments, the modified kudzu fiber is specifically prepared by treating the kudzu fiber with an alkali solution, silanizing the obtained solid phase, and washing and drying it.

[0049] In some embodiments, the alkali solution treatment of kudzu fiber specifically includes:

[0050] Mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 0.5 to 1.5 hours, preferably 1 hour, washing, and freeze-drying to obtain a solid phase;

[0051] Wherein, the pH of the alkali solution is 9 to 11, preferably 10;

[0052] The solid phase silanization specifically comprises:

[0053] The solid phase and silanol are mixed, stirred at 40-60° C. for 2-3 hours, preferably at 50° C. for 2.5 hours, washed, freeze-dried, and the modified kudzu fiber is obtained.

[0054] A second aspect of the present application provides a method for preparing a degradable plastic masterbatch, comprising the following steps:

[0055] The coupling agent is stirred and mixed with starch, and then stirred and mixed with modified kudzu fiber and polylactic acid. The solid phase is then added into a twin-screw extruder unit for mixing and extrusion. The extruded long strip sample is pelletized, and the pelletization is repeated at least once.

[0056] In some embodiments, the mass ratio of the modified kudzu fiber, polylactic acid, starch, and coupling agent is (0.1-15): (80-95): (5-15): (0.5-2), preferably 10:85:4:1. The particle size of the modified kudzu fiber is 500 μm to 2700 μm, preferably 500 μm, and the molecular weight of the polylactic acid is a weight average molecular weight of 5 to 19×10 5 g / mol, the starch is corn starch or cassava starch, preferably corn starch, and the coupling agent is one or more of KH550 silane coupling agent, KH560 silane coupling agent, KH570 silane coupling agent, titanate coupling agent TTS, titanate coupling agent 201, and aluminate coupling agent, preferably KH550 silane coupling agent. The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 0.5 to 1.5 hours, preferably for 1 hour, washing, and freeze-drying to obtain a solid phase; wherein the pH of the alkali solution is 9 to 11, preferably 10. Then, the solid phase and silanol are mixed, stirred at 40 to 60°C for 2 to 3 hours, preferably at 50°C for 2.5 hours, washed, freeze-dried, and the modified kudzu fiber is obtained.

[0057] In some embodiments, the coupling agent and starch are mixed at a temperature of 80 to 120°C, preferably 100°C, for a mixing time of 10 to 20 minutes, preferably 15 minutes, and the mixing container is a high-speed mixer. The mixing temperature with the modified kudzu fiber and polylactic acid is room temperature, for a mixing time of 5 to 10 minutes, preferably 8 minutes, and the mixing container is a high-speed mixer. The screw aspect ratio of the twin-screw extruder is 40 to 60, preferably 50, and the screw speed is 20 to 40 rpm, preferably 30. The temperatures of the eight heating zones and the die head of the twin-screw extruder are 130, 135, 140, 145, 150, 160, 165, 165, and 155°C, respectively.

[0058] A third aspect of the embodiments of the present application provides a degradable plastic masterbatch obtained by the preparation method of the degradable plastic masterbatch as described above.

[0059] A fourth aspect of the embodiments of the present application provides an application of a degradable plastic masterbatch in the preparation of a plastic film.

[0060] The above implementation is described in more detail below in conjunction with specific examples.

[0061] Example 1

[0062] KH550 silane coupling agent and corn starch were added into a high-speed mixer and mixed at 100°C for 15 min. Then, modified kudzu fiber with a particle size of 500 μm and a weight-average molecular weight of 10×10 5 g / mol of polylactic acid was mixed with high-speed stirring at room temperature for 15 minutes, wherein the mass ratio of modified kudzu fiber, polylactic acid, corn starch and coupling agent was 10:85:4:1. The solid phase was then added to a twin-screw extruder unit for mixed extrusion. The screw aspect ratio of the screw extruder unit was 50, the screw speed was 30 rpm, and the temperatures of the eight heating zones and the die of the twin-screw extruder unit were 130, 135, 140, 145, 150, 160, 165, 165, and 155 °C, respectively. The extruded long strip sample was pelletized and the granulation was repeated once.

[0063] The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 1 hour, washing, and freeze-drying to obtain a solid phase, wherein the pH of the alkali solution is 9 to 11, preferably 10, and then mixing the solid phase and silanol, stirring at 50°C for 2.5 hours, washing, and freeze-drying to obtain the modified kudzu fiber.

[0064] Example 2

[0065] KH550 silane coupling agent and corn starch were added into a high-speed mixer and mixed at 100°C for 15 min. Then, modified kudzu fiber with a particle size of 2700 μm and a weight-average molecular weight of 10×10 5 g / mol of polylactic acid was mixed with high-speed stirring at room temperature for 15 minutes, wherein the mass ratio of modified kudzu fiber, polylactic acid, corn starch and coupling agent was 10:85:4:1. The solid phase was then added to a twin-screw extruder unit for mixed extrusion. The screw aspect ratio of the screw extruder unit was 50, the screw speed was 30 rpm, and the temperatures of the eight heating zones and the die of the twin-screw extruder unit were 130, 135, 140, 145, 150, 160, 165, 165, and 155 °C, respectively. The extruded long strip sample was pelletized and the granulation was repeated once.

[0066] The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 1 hour, washing, and freeze-drying to obtain a solid phase, wherein the pH of the alkali solution is 9 to 11, preferably 10, and then mixing the solid phase and silanol, stirring at 50°C for 2.5 hours, washing, and freeze-drying to obtain the modified kudzu fiber.

[0067] Comparative Example 1

[0068] KH550 silane coupling agent and corn starch were added into a high-speed mixer and mixed at 100°C for 15 min. Then, modified kudzu fiber with a particle size of 3000 μm and a weight-average molecular weight of 10×10 5 g / mol of polylactic acid was mixed with high-speed stirring at room temperature for 15 minutes, wherein the mass ratio of modified kudzu fiber, polylactic acid, corn starch and coupling agent was 10:85:4:1. The solid phase was then added to a twin-screw extruder unit for mixed extrusion. The screw aspect ratio of the screw extruder unit was 50, the screw speed was 30 rpm, and the temperatures of the eight heating zones and the die of the twin-screw extruder unit were 130, 135, 140, 145, 150, 160, 165, 165, and 155 °C, respectively. The extruded long strip sample was pelletized and the granulation was repeated once.

[0069] The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 1 hour, washing, and freeze-drying to obtain a solid phase, wherein the pH of the alkali solution is 9 to 11, preferably 10, and then mixing the solid phase and silanol, stirring at 50°C for 2.5 hours, washing, and freeze-drying to obtain the modified kudzu fiber.

[0070] Comparative Example 2

[0071] KH550 silane coupling agent and corn starch were added into a high-speed mixer and mixed at 100°C for 15 min. Then, modified kudzu fiber with a particle size of 400 μm and a weight-average molecular weight of 10×10 5 g / mol of polylactic acid was mixed with high-speed stirring at room temperature for 15 minutes, wherein the mass ratio of modified kudzu fiber, polylactic acid, corn starch and coupling agent was 10:85:4:1. The solid phase was then added to a twin-screw extruder unit for mixed extrusion. The screw aspect ratio of the screw extruder unit was 50, the screw speed was 30 rpm, and the temperatures of the eight heating zones and the die of the twin-screw extruder unit were 130, 135, 140, 145, 150, 160, 165, 165, and 155 °C, respectively. The extruded long strip sample was pelletized and the granulation was repeated once.

[0072] The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 1 hour, washing, and freeze-drying to obtain a solid phase, wherein the pH of the alkali solution is 9 to 11, preferably 10, and then mixing the solid phase and silanol, stirring at 50°C for 2.5 hours, washing, and freeze-drying to obtain the modified kudzu fiber.

[0073] Comparative Example 3

[0074] KH550 silane coupling agent and corn starch were added into a high-speed mixer and mixed at 100°C for 15 min. Then, kudzu fiber with a particle size of 500 μm and a weight-average molecular weight of 10×10 5 g / mol of polylactic acid was mixed with high-speed stirring at room temperature for 15 minutes, wherein the mass ratio of kudzu fiber, polylactic acid, corn starch and coupling agent was 10:85:4:1. The solid phase was then added to a twin-screw extruder for mixed extrusion. The screw aspect ratio of the screw extruder was 50, the screw speed was 30 rpm, and the temperatures of the eight heating zones and the die of the twin-screw extruder were 130, 135, 140, 145, 150, 160, 165, 165, and 155 °C, respectively. The extruded long strip sample was pelletized and the granulation was repeated once.

[0075] Comparative Example 4

[0076] KH550 silane coupling agent and corn starch were added into a high-speed stirrer and mixed at 100°C for 15 min. Then, a 10×10 5 g / mol of polylactic acid was mixed with high-speed stirring at room temperature for 15 minutes, wherein the mass ratio of polylactic acid, corn starch and coupling agent was 85:4:1. The solid phase was then added to a twin-screw extruder for mixed extrusion. The screw aspect ratio of the screw extruder was 50, the screw speed was 30 rpm, and the temperatures of the eight heating zones and the die of the twin-screw extruder were 130, 135, 140, 145, 150, 160, 165, 165, and 155 °C, respectively. The extruded long strip sample was pelletized and the granulation was repeated once.

[0077] Comparative Example 5

[0078] The modified kudzu fiber with a corn starch particle size of 500 μm and a weight average molecular weight of 10×10 5g / mol of polylactic acid are stirred at high speed at room temperature for 15 minutes (in a high-speed mixer), wherein the mass ratio of modified kudzu fiber, polylactic acid and corn starch is 10:85:4, and then the solid phase is added to a twin-screw extruder unit for mixed extrusion. The screw aspect ratio of the screw extruder unit is 50, the screw speed is 30rpm, and the temperatures of the eight heating zones and the head of the twin-screw extruder unit are 130, 135, 140, 145, 150, 160, 165, 165, and 155°C, respectively. Then the extruded long strip sample is pelletized and the granulation is repeated once.

[0079] The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 1 hour, washing, and freeze-drying to obtain a solid phase, wherein the pH of the alkali solution is 9 to 11, preferably 10, and then mixing the solid phase and silanol, stirring at 50°C for 2.5 hours, washing, and freeze-drying to obtain the modified kudzu fiber.

[0080] Characterization example

[0081] 1. Mechanical properties analysis

[0082] According to ASTM D882 standard, the mechanical properties of the composite film were measured at room temperature using a universal mechanical testing machine, with a test speed of 2 mm / min and a load cell of 450 N. Each sample was tested 5 times, and the test results are shown in the following table.

[0083] Tensile strength(MPa) Elongation at break (%) Example 1 34.5 1.6 Example 2 22.7 1.8 Comparative Example 1 18.2 2.0 Comparative Example 2 34.6 1.8 Comparative Example 5 30.8 1.7

[0084] As can be seen from the above table, reducing the particle size of the modified kudzu fiber increases its mechanical properties, but the increase is not large to a certain extent. This is because the bonding strength of the interface between the modified kudzu fiber and the polylactic acid composite material affects the mechanical properties of the composite material, and the interface bonding strength of the composite material is mainly affected by the two factors of the interface bonding strength and interface friction between the modified kudzu fiber and the polylactic acid. For the same type of fiber, the smaller the particle size, the larger the specific surface area of ​​the modified kudzu fiber, the larger the contact area with the PLA matrix, the greater the interface friction, the stronger the interface bonding strength, and finally the stronger the mechanical properties of the plastic. For the same type of fiber, the larger the particle size, the greater the degree of entanglement between the fibers, the more difficult it is for the fibers to disperse in the polylactic acid, thereby forming pores in the plastic, and thus reducing the tensile strength of the plastic. However, when the particle size is too small, since the modified kudzu fiber contains a large number of hydroxyl groups, agglomeration will occur, which makes the modified kudzu fiber unevenly dispersed in the polylactic acid, forming an interface separation phenomenon, affecting the mechanical properties of the plastic. The elongation at break is reduced when the particle size of modified kudzu fiber is reduced. This is mainly because the addition of modified kudzu fiber destroys the movement of the polylactic acid chain, thereby improving the rigidity of the masterbatch. However, if the particle size is too large, it may lead to agglomeration, and the elongation at break will increase. If the particle size is too small, it may be too dispersed, resulting in an increase in the elongation at break. Without the addition of coupling agent, the coupling agent cannot fully react with the hydroxyl group on the surface of corn starch to form a high molecular organic film. If the surface of corn starch is not treated with non-polarity, the interfacial bonding effect of the mixture cannot be improved, resulting in poor mechanical properties.

[0085] 2. Water absorption analysis

[0086] The water absorption rate was determined according to ASTM D570-98 (2018) standard. The masterbatch extrusion films of the embodiment and the comparative example and the pure polylactic acid film were immersed in deionized water at 25°C for 24 hours. Each sample was measured at least 5 times. The specific calculation formula of the water absorption rate is:

[0087]

[0088] Where W is the water absorption rate, M a is the mass after water absorption, M d It is the mass before water absorption.

[0089] Water absorption (%) Pure polylactic acid film 0.72 Example 1 0.56 Comparative Example 3 2.4677 Comparative Example 4 0.89

[0090] The water absorption of pure polylactic acid film is greater than 0, because there are a large number of ester groups in polylactic acid, which will form hydrogen bonds with water molecules. The water absorption without adding modified kudzu fiber does not change much. With the addition of kudzu fiber (Comparative Example 3), the water absorption of plastic gradually increases. This is because kudzu fiber has a large number of hydroxyl groups, which will attract water molecules, so that water molecules enter the composite film, allowing plastic to expand, thereby promoting the formation of microcavities in the composite film. At the same time, the microcavities produced by plastics will further accelerate the penetration of water molecules into the composite film, and finally increase the water absorption. After kudzu fiber is modified, it is found that the water absorption suddenly decreases. This is because KH-550 and NaOH treatment reduce the number of hydroxyl groups on the surface of modified kudzu fiber, so that the modified kudzu fiber is evenly dispersed in the polylactic acid matrix, so that the formed plastic surface is smoother, preventing water molecules from entering plastic. On the other hand, the surface treatment makes the surface of the kudzu root fiber rough, making the modified kudzu root fiber and polylactic acid more closely combined, reducing the gap between the modified kudzu root fiber and the polylactic acid matrix, thereby preventing the diffusion of water molecules between the modified kudzu root fiber and the polylactic acid.

[0091] 3. Anti-ultraviolet performance

[0092] Anti-ultraviolet performance is an important indicator for measuring food packaging materials. Polylactic acid is one of the most commonly used polymers in packaging materials. However, the poor anti-ultraviolet performance of polylactic acid film greatly limits its application. When the sun emits a wavelength of 100 to 400nm, ultraviolet radiation occurs. The transmittance of the composite film was tested using a UV-visible spectrophotometer with a test wavelength range of 200-800nm ​​and a scanning rate of 100nm / min. The ultraviolet transmittance of pure polylactic acid film, embodiment and comparative example masterbatch extrusion film is shown in the following table:

[0093] UVA UVB Pure polylactic acid film 89.6 85.7 Example 1 85.1 81.8 Comparative Example 3 84.8 80.8 Comparative Example 4 88.6 84.9

[0094] It can be seen from the above table that adding modified kudzu fiber and kudzu fiber can effectively improve the UV shielding performance of plastics. This is because the fiber absorbs ultraviolet rays, and the increase of fibers will cause the fibers to agglomerate and entangle with each other, which can also effectively shield ultraviolet rays. When no fibers are added, the shielding function is not great.

[0095] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A degradable plastic masterbatch, characterized in that: It comprises the following components in parts by weight: The modified kudzu fiber is specifically prepared by treating the kudzu fiber with an alkali solution to obtain a solid phase, mixing the solid phase with silanol, stirring at 40 to 60° C. for 2 to 3 hours, and washing and drying; The alkali solution treatment of kudzu fiber specifically includes: mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 0.5 to 1.5 hours, washing, freeze-drying to obtain a solid phase; wherein the pH of the alkali solution is 9 to 11.

2. A degradable plastic masterbatch according to claim 1, characterized in that: The degradable plastic masterbatch comprises the following components in parts by weight:

3. A degradable plastic masterbatch according to claim 1 or 2, characterized in that: The particle size of the modified kudzu fiber is 500 μm to 2700 μm.

4. A degradable plastic masterbatch according to any one of claims 1 or 2, characterized in that: The molecular weight of the polylactic acid is 5 to 19×10 5 g / mol.

5. The degradable plastic masterbatch according to any one of claim 1, characterized in that: The coupling agent is one or more of KH550 silane coupling agent, KH560 silane coupling agent, KH570 silane coupling agent, titanate coupling agent TTS, titanate coupling agent 201, and aluminate coupling agent.

6. A method for preparing a degradable plastic masterbatch, characterized in that: The following steps are involved: The coupling agent is stirred and mixed with starch, and then stirred and mixed with modified kudzu fiber and polylactic acid, and then the solid phase is added to a twin-screw extruder unit for mixing and extrusion, and then the extruded long strip sample is pelletized, and the pelletization is repeated at least once; The modified kudzu fiber is specifically prepared by mixing kudzu fiber and sodium hydroxide solution, ultrasonicating for 0.5 to 1.5 hours, washing and freeze-drying to obtain a solid phase, wherein the pH value of the alkaline solution is 9 to 11, then mixing the solid phase and silanol, stirring at 40 to 60° C. for 2 to 3 hours, washing and freeze-drying to obtain the modified kudzu fiber.

7. The method for preparing a degradable plastic masterbatch according to claim 6, characterized in that: The mass ratio of the modified kudzu fiber, polylactic acid, starch and coupling agent is (0.1-15): (80-95): (5-15): (0.5-2); And / or, the molecular weight of the polylactic acid is a weight average molecular weight of 5 to 19×10 5 g / mol; And / or, the coupling agent is one or more of KH550 silane coupling agent, KH560 silane coupling agent, KH570 silane coupling agent, titanate coupling agent TTS, titanate coupling agent 201, and aluminate coupling agent.

8. The method for preparing a degradable plastic masterbatch according to claim 6, characterized in that: The coupling agent and starch are mixed at a temperature of 80 to 120°C, for a mixing time of 10 to 20 minutes, and the mixing container is a high-speed mixer; and / or, the mixing temperature with the modified kudzu fiber and polylactic acid is room temperature, the mixing time is 5 to 10 minutes, and the mixing container is a high-speed mixer; And / or, the screw aspect ratio of the twin-screw extruder is 40-60, and the screw speed is 20-40 rpm; And / or, the temperatures of the eight heating zones and the die of the twin-screw extruder are 130, 135, 140, 145, 150, 160, 165, 165, and 155° C., respectively.

9. A degradable plastic masterbatch obtained by the preparation method of the degradable plastic masterbatch as claimed in any one of claims 6 to 8.

10. Use of the degradable plastic masterbatch according to claim 1 or 9 in preparing plastic film.

Citation Information

Patent Citations

  • Nano carbon aerogel modified cyanobacteria-based composite bioplastic and preparation method thereof

    CN106118000A

  • Environment-friendly degradable cotton cellulose plastic film as well as preparation method and application thereof

    CN111848998A

  • Degradable plastic prepared from plant wood fibers and preparation method thereof

    CN116144191A

  • Kudzu root nanocellulose fiber-polylactic acid plastic film and preparation method thereof

    CN107033562A

  • Composite toughened polylactic acid degradable master batch as well as preparation method and application thereof

    CN117050494A